Pengaruh Kemudahan dan Manfaat Bertransaksi Menggunakan Kode QR terhadap Keputusan Penggunaan Quick Response Indonesian Standard (QRIS) pada Mahasiswa Fakultas Ilmu Sosial dan Politik Universitas Riau - Dwi Nur; Meyzi Heriyanto (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2025)
This study aims to determine the effect of the convenience and benefits of transactions using QR codes on decisions to use the Quick Response Indonesian Standard (QRIS) on students of the Faculty of Social and Political Sciences, Riau University partially and simultaneously. This study uses a quantitative approach by distributing questionnaires to 130 respondents who have used or often use QRIS. Sampling this study using non-probability sampling method, namely by purposive sampling. This study uses multiple linear regression analysis methods with SPSS version 29. The results showed that the convenience variable has a significant influence on usage decisions and the benefit variable has a significant influence on usage decisions. Simultaneous testing found that the convenience and benefit variables together had a significant influence on the decision to use QRIS on students of the Faculty of Social and Political Sciences, Riau University. The coefficient of determination test results show a value of 43.8%. The remaining 56.2% is explained by other variables outside the study.